"Gendering" contamination: physical, social and moral taint in the context of COVID-19. Issue 7 (24th September 2020) - Simpson, Ruth; Morgan, Rachel
Abstract : Purpose: The purpose of this paper is to explore the "gendering" of contamination in the context of COVID-19 where "gendering" is taken to include other, cross-cutting areas of disadvantage. Design/methodology/approach: This paper draws on secondary sources to explore gender and COVID-19. Findings: The authors show that contamination is rooted in structural disadvantage, reproducing classed, gendered and racial difference in terms of how it is encountered and experienced. Practical implications: This "thought piece" suggests a greater awareness of how pandemics and other public health emergencies impact of structural disadvantages. Originality/value: This "thought piece" applies notions of taint to a contemporary pandemic that has had far-reaching consequences for issues of equality.